A comparison of the burden of knee osteoarthritis attributable to high body mass index in China and globally from 1990 to 2019 - Song, Min; Chen, Huijing; Li, Jingyi; Han, Weichang; Wu, Wenfeng; Wu, Gaoyi; Zhao, Anqi; Yuan, Qing; Yu, Jiani (Frontiers in Medicine, 2023)
Background: Excess BMI plays a key role in the onset and progression of knee OA. However, the burden of knee OA attributable to high BMI at the global, Chinese, and regional levels have received far too little attention. This study is to provide evidence to support the design of policy by investigating long-term trends of YLDs for knee OA. Methods: To illustrate the trends of YLDs for knee OA attributable to high BMI and the temporal trends of the YLDs rate by age, period, and cohort, Joinpoint and APC were used to analyze the YLDs data of knee OA from the GBD 2019. Results: In China, there were 549,963.5 YLDs for knee OA attributable to high BMI in 2019, which had increased by 460.7% since 1990. From 1990 to 2019, ASDR of knee OA attributable to high BMI trended upwards. The AAPC of knee OA attributable to high BMI in China and globe were 3.019%, 1.419% respectively. The longitudinal age curve of the APC model showed that the YLDs rates of knee OA due to high BMI increased with age, and YLDs rates were higher among females than males. The RRs of knee OA due to high BMI increased significantly. The cohort RRs of knee OA due to high BMI increased among those born between 1900 and 1970. The net drifts of knee OA attributable to high BMI in China and globe were above 1. Compared with global condition, the net drift values of knee OA attributable to high BMI in China was higher. Compared with females, males had higher net drift value. Countries with high SDI have a much higher burden of knee OA caused by high BMI than countries with low SDI. Conclusions: In China, high BMI is a substantial cause of knee OA, the incidence of which has been increasing since 1990. Women and the elderly are more vulnerable to knee OA. The Chinese government must take the long-term impact of high BMI on knee OA into account and implement effective public health policies and resort to interventions to reduce the burden as soon as possible.